A legal review on the law pertaining to negligent bus drivers / Zainul Ariffin Zulkifli, Siddique Hakeem Khairudin and Ahmad Faiz Fitri Mohamad. - Zulkifl, Zainul Ariffin; Khairudin, Siddique Hakeem; Mohamad, Ahmad Faiz Fitri (2011)
The accidents in Simpang Ampat and Cameron Highlands have shocked the nation. Although Malaysia does not have a proud record on deaths on the road but these accidents have come as a huge surprise due to its horrifying nature. Despite having one of the best road structures, our road accidents statistic and deaths counts are very high compared to other nations. Up until today, there are only few researches or studies that have been conducted to evaluate the effectiveness of the current law in Malaysia especially those regarding negligent act of bus drivers. For now, most studies only concern about the causes and contributing factors of accidents in general and the conditions of the roads in Malaysia. Hence, this study has been conducted to analyze the current law regulating bus drivers and the government agencies involved in enforcing those laws. Not only that, this study will also touch on the causes of accidents especially those involving buses. It is important to know the contributing factors of bus accidents since express bus is one of the main modes for long distance transportation for middle class society in Malaysia. Besides, when the causes of bus accidents have been determine, it would be much easier for us to suggest the appropriate solutions to address this issue. The data analysis in this study is done using internet research and readings from selected articles in the country and abroad. Information was also gathered from newspaper.